The Impact of Active Deep Learner Experience on Learning in Elementary Schools - Arta Mulya Budi Harsono (Institut Agama Islam Negeri Palopo, 2025)
This study was motivated by the widespread diffusion of innovation in learning, particularly in elementary schools. Innovation in learning is a crucial and potential necessity as a step toward improving the quality of education. One form of innovation that has emerged in learning is the application of Adaptive Deep Learner Experience (ADLX) learning. This study employs a literature review method, involving the screening of previous studies related to the implementation of ADLX in elementary school education. Data collection was conducted through the extraction of relevant information from each literature source, including reputable national and international journals. The data obtained were then analyzed qualitatively. This study aims to explore and synthesize the impact of ADLX implementation on learning in elementary schools. The results of the study indicate that the continuous implementation of ADLX has a positive impact in various aspects related to learning in elementary schools. The implication of these findings is that ADLX has great potential as an innovative and effective learning alternative to be applied in elementary school education.